Quantifying Contextual Interference and Its Effect on Skill Transfer in Skilled Youth Tennis Players - Buszard, Tim; Reid, Machar; Krause, Lyndon; Kovalchik, Stephanie; Farrow, Damian (Frontiers in Psychology, 2017)
The contextual interference effect is a well-established motor learning phenomenon. Most of the contextual interference effect literature has addressed simple skills, while less is known about the role of contextual interference in complex sport skill practice, particularly with respect to skilled performers. The purpose of this study was to assess contextual interference when practicing the tennis serve. Study 1 evaluated tennis serve practice of 9 skilled youth tennis players using a novel statistical metric developed specifically to measure between-skill and within-skill variability as sources of contextual interference. This metric highlighted that skilled tennis players typically engaged in serve practice that featured low contextual interference. In Study 2, 16 skilled youth tennis players participated in 10 practice sessions that aimed to improve serving “down the T”. Participants were stratified into a low contextual interference practice group (Low CI) and a moderate contextual interference practice group (Moderate CI). Pre- and post-tests were conducted one week before and one week after the practice period. Testing involved a skill test, which assessed serving performance in a closed setting, and a transfer test, which assessed serving performance in a match-play setting. No significant contextual interference differences were observed with respect to practice performance. However, analysis of pre- and post-test serve performance revealed significant Group x Time interactions. The Moderate CI group showed no change in serving performance (service displacement from the T) from pre- to post-test in the skill test, but did display improvements in the transfer test. Conversely, the Low CI group improved serving performance (service displacement from the T) in the skill test but not the transfer test. Results suggest that the typical contextual interference effect is less clear when practicing a complex motor skill, at least with the tennis serve skill evaluated here. We encourage researchers and applied sport scientists to use our statistical metric to measure contextual interference.